Holocene hydro-climatic variability in the Mediterranean: A synthetic multi-proxy reconstruction. (May 2019) - Finné, Martin; Woodbridge, Jessie; Labuhn, Inga; Roberts, C Neil
Here we identify and analyze proxy data interpreted to reflect hydro-climatic variability over the last 10, 000 years from the Mediterranean region to (1) outline millennial and multi-centennial-scale trends and (2) identify regional patterns of hydro-climatic variability. A total of 47 lake, cave, and marine records were transformed to z -scores to allow direct comparisons between sites, put on a common time scale, and binned into 200-year time slices. Six different regions were identified based on numerical and spatial analyzes of z -scores: S Iberia and Maghreb, N Iberia, Italy, the Balkans, Turkey, and the Levant, and the overall hydro-climate history of each region was reconstructed. N Iberia is largely decoupled from the five other regions throughout the Holocene. Wetter conditions occur in the five other regions between 8500 and 6100 yr BP. After 6000 yr BP, climate oscillated until around 3000 ± 300 yr BP, which seems to have been the overall driest period in the eastern Mediterranean and North Africa. In contrast, Italy and N Iberia seem to have remained wetter during this period. In addition, non-metric multidimensional scaling (nMDS) was applied to 18 long, continuous climate z -score records that span the majority of the Holocene. nMDS axes 1 and 2 illustrate the main trends in the z -score data. The first axis captures a long-term development of drier condition in the Mediterranean from 7900 to 3700 yr BP. Rapid shifts occur in nMDS axis 2 at 6700–6300 BP, 4500–4300 BP, and 3500–3300 BP indicating centennial-scale climate change. Our synthesis highlights a dominant south/east versus north/west Mediterranean hydro-climate dipole throughout the Holocene and therefore confirms that there was no single climate trajectory characterizing the whole Mediterranean basin during the last 10 millennia.